Antisemitism-Islamophobia: labels, accusations, and prejudice in the Israel-Hamas war - Hedges, Paul (2024)
In the current Israel-Hamas war, accusations of antisemitism and Islamophobia are deployed by global advocates on each side. Such accusations are, however, often more political than substantive, though serious prejudice does exist and must be countered.